Mathématiques
najihs
6

Merci de votre aide !!!!!!!!!!!! A= 3x (2x - 5) - (6x+1) (-2x+4) B= -5x + 3 - (3-5x) + (x+1)² C= (3x-7)² - (3x-7)(3x+7)

+0
(1) Réponses
galeleeseuwo

A= 3x (2x - 5) - (6x+1) (-2x+4) a = 6x²-15x-(-12x²+24x-2x+4) a = 6x²-15x +12x² -22x-4 a = 18x² -27x -4 B= -5x + 3 - (3-5x) + (x+1)² b = -5x+3 -3+5x +x²+2x+1 b = x² +2x +1 C= (3x-7)² - (3x-7)(3x+7) c = 9x² -42x +49 - (9x²+21x-21x-49) c =9x² +42x+49 -9x² +9 c = 42x + 58 il faut que tu utilises les identites remarquables

Ajouter une réponse